2021
DOI: 10.3389/fvets.2021.634577
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genome-Wide Alternative Splicing Analysis of Longissimus Dorsi Muscles Between Japanese Black (Wagyu) and Chinese Red Steppes Cattle

Abstract: Alternative splicing is a ubiquitous regulatory mechanism in gene expression that allows a single gene generating multiple messenger RNAs (mRNAs). Significant differences in fat deposition ability and meat quality traits have been reported between Japanese black cattle (Wagyu) and Chinese Red Steppes, which presented a unique model for analyzing the effects of transcriptional level on marbling fat in livestock. In previous studies, the differentially expressed genes (DGEs) in longissimus dorsi muscle (LDM) sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…He et al (2021) analyzed Chinese Simmental cattle and found that CPT1B was significantly associated with back fat thickness and arachidonic acid. Wang et al (2021) and Fang et al (2021) also showed that CPT1B was associated with meat quality traits in cattle. PFN1 , GNAS , and PLINS have been associated with beef tenderness and intermuscular fat (Imumorin et al, 2011; Malheiros et al, 2021; Xiong et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…He et al (2021) analyzed Chinese Simmental cattle and found that CPT1B was significantly associated with back fat thickness and arachidonic acid. Wang et al (2021) and Fang et al (2021) also showed that CPT1B was associated with meat quality traits in cattle. PFN1 , GNAS , and PLINS have been associated with beef tenderness and intermuscular fat (Imumorin et al, 2011; Malheiros et al, 2021; Xiong et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…Significant differences in GADD45A expression were also found in the muscle transcriptional profiles of marbled and lean beef, corresponding to different lipid metabolic processes [ 35 ]. NR4A1 was enriched in the Gene Ontology terms related to muscle development in beef cattle [ 36 ]. VEGFA was found to contribute to increasing adiposity in Iberian pig [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In China, the frozen semen of Wagyu is used for crossing with native breeds to produce crossbred offspring with good meat quality traits (Li et al, 2013; Wang et al, 2019). Previous studies used SNP arrays (Ishii et al, 2013; Kawaguchi et al, 2022) and transcriptome sequencing (Fang et al, 2021) to identify molecular markers and genes that correlated with meat quality traits. However, no studies have used whole‐genome sequencing (WGS) data to identify genomic variations in Wagyu.…”
Section: Figurementioning
confidence: 99%